The Weight of History - Offen, Julia L. (Lidé města, 2022)
This is a short work of creative ethnographic prose that relies solely upon crafted narrative to show rather than explain its message. In the mid 1990s, I spent two years doing ethnographic fieldwork with European traveling circuses. One troupe I worked in for a considerable amount of time included members of 16 different nationalities. They had a posted rule banning the display of national flags or symbols within their circus community, and – other than some fleeting heated moments during World Cup soccer – seemed to keep conflicts by nationality group to a minimum. Nonetheless, historical tensions rested barely under the surface. Although none of the people portrayed here were alive for the events of WWII, that conflict still echoed down into everyday life in the circus over 50 years later. This story is based upon actual characters and events the author experienced, although all individuals’ names and some identifying characteristics have been changed.